Предмет: Математика,
автор: Valeriakirillova475
(х-3)²+(х+2)²=2(3-х)(х+2)
Ответы
Автор ответа:
0
х²-6х+х²+4х+4=(6-2х)(х+2)
2х²-2х+13=6х+12-2х²-4х
2х²-2х+13-2х-12+2х²=0
4х²-4х+1=0
(2х-1)²=0
2х-1=0
2х=1
х=½
2х²-2х+13=6х+12-2х²-4х
2х²-2х+13-2х-12+2х²=0
4х²-4х+1=0
(2х-1)²=0
2х-1=0
2х=1
х=½
Похожие вопросы
Предмет: Геометрия,
автор: arinadanilchenko453
Предмет: Английский язык,
автор: kr1omanser1337
Предмет: Биология,
автор: yarik0413
Предмет: Алгебра,
автор: мачо1000000
Предмет: Алгебра,
автор: sopovakaterina